Rb-Sr Isotopic Geochronology and Geological Implications of Dongfeng Gold Deposit in Jiaodong Area (2016)
The superlarge Dongfeng gold deposit is located in the Potouqing faults-alteration belt of the eastern part of the ‘Zhao-Lai-gold ore belt’, which belongs to the northwestern part of the Jiaodong area. Tectonically, ore bodies are controlled by faults and gold mainly occurs in the pyrite and polymetallic sulfide-bearing quartz vein. In this paper, Rb–Sr isotopic analysis is carried out with the beresite, which formed by hydrothermal metasomatism, and the Rb–Sr isochron age is 125.5±6.7Ma, indicating this deposit set up in the early Cretaceous of the late Yanshanian. Based on the relationship between the Dongfeng gold deposit and the Mesozoic granite, it is suggested that the formation of the gold deposit is a complex geological process of gradual enrichment and precipitation of the ore-forming elements. The initial 87Sr/86Sr ratio of the beresite is 0.711502±0.000069, which indicates the ore-forming materials mainly come from the crust. Combined with the complex mineralization process of the Dongfeng gold deposit and the reported H-O isotopic data, it is suggested that the ore-forming materials are mainly derived from the crust with some mantle materials, while the ore-forming fluids are originated primarily from magmatic hydrothermal and mantle with some precipitate water.